Assessment of Genetic Relationship of some Horseshoe Bats (Chiroptera: Rhinolophidae) in Vietnam Using Cytochromoxydase Subunit I (COI) Gene Sequence - Nga, Tran Thi; Anh, Tran Thi Thuy; Huyen, Do Thi Thanh; Son, Nguyen Truong; Thong, Vu Dinh; Sang, Nguyen Vang; Thanh, Hoang Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: DNA barcoding was used to examining the genetic relationship between some Rhinolophus bat taxa ( R. malayanus, R. cf. malayanus, R. marshalli, R. cf. marshalli ) in Vietnam using cytochrome oxidase-I ( COI ) gene sequence. Through this study, we constructed the phylogenic trees and analysed genetic relationships between some Rhinolophus taxa collected in Vietnam. The obtained phylogenetic tree showed two well-defined clusters. The genetic distances between species varied from 2.7% to 16.3%. The smallest distances were recorded between species from the same group whereas the largest distances were between species from the different groups. Genetic data supported the previous conclusion based on morphological classification of R. malayanus, R. cf. malayanus, R. marshalli, R. cf. marshalli . Keywords: Genetic relationship, COI gene, Rhinolophus , Vietnam.